Do natural disasters enhance societal trust? - Hideki Toya; Mark Skidmore (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper we investigate the long-run relationship between disasters and societal trust. A growing body research suggests that factors such as income inequality, ethnic fractionalization, and religious heritage are important determinants of social capital in general, and trust in particular. We present new cross-country evidence of another important determinant of trust - the frequency of natural disasters. Frequent naturally occurring events such as storms require (and provide opportunity for) societies to work closely together to meet their challenges. While severe storms can have devastating human and economic impacts, a potential spillover benefit of greater storm exposure may be a more tightly knit society.
Keywords: O10; Q54; 330; natural disasters; economic development; social capital; trust